Later novels and other writings - Chandler, Raymond (The Library of America, 1995)
This volume also contains a screenplay, Double Indemnity, and a few essays and letters. The essays "The Simple Art of Murder", and "Writers in Hollywood" should be required reading for anyone interested in 20th century culture, movies, and literature